Grave secrets - Reichs, Kathy (London : Arrow, 2002)
Facing the most heartbreaking case of her career, Temperance Brennan investigates shallow graves where fading clues begin to emerge of a brutal crime that was committed more than two decades ago.
Library Journal
Publisher's Weekly
Wilson's Fiction
Adult
Adult
Keywords: Americans -- Guatemala -- Fiction; Brennan, Temperance (Fictitious character) -- Fiction; Forensic anthropology -- Fiction; Mayas -- Fiction; Women anthropologists -- Fiction; Americans -- Guatemala -- Fiction; Brennan, Temperance (Fictional character) -- Fiction; Forensic sciences -- Fiction; Mayas -- Fiction; Mystery fiction; Native Americans -- Central America -- Fiction; Women anthropologists -- Fiction; Guatemala -- Fiction; Guatemala -- Fiction; Mystery fiction